The Impacts of ALMA Primary Variables on Profitability An Empirical Study of Indonesian Banking - Jumono, Sapto; Achsani, Noer Azam; Hakim, Dedi Budiman; Firdaus, Muhamad (International Research Journal of Business Studies, 2015)
This study aims to determine the impact of liquidity on BEP and ROE in Indonesian banking industry. The supporting theory in this study is ALMA theory. Based on annual data for the period 2001-2014 and following purposive sampling technique, the acquired amount of sample study is 97 banks. The data is analyzed using panel data regression of GMM Arrelano Bond, as a novelty in data processing, therefore the speed of adjustment can be known. The ALMA variables such as LAR, capital, leverage, operating expenses, interest income, and CAR sensitivity have a significant effect on BEP and ROE. Meanwhile LDR, NPL, the FBI have no impact on profitability. The implication of this study is the fact that banking performance in Indonesia can be leveled up through the reduction in mortgage interest rates and increment of credit volume and FBI.